YOGYAKARTA CITY AS A SMART DESTINATION TOURIST - Alvin, Giovanni; Budisetyorini, Beta; Sopian, Tatang (Politeknik Pariwisata NHI Bandung, 2022)
The application of smart cities has become a trend in regional planning in Indonesia. The current condition of urban development planning is more focused on environmental and social aspects of sustainability of the problems of today which are directly related to problems urban. Such as the decline in the quality of public services, the reduced availability of land settlements, road congestion, difficulty finding parking spaces, increased consumption of energy, waste pollution, increased crime rates, and other social problems. Thus, to be able to solve these problems, planning is needed One of the smarter developments is through smart cities. One of the development sectors which has become a priority for the last 5 years is the tourism sector. Where in the field tourism is known as the Smart Tourism concept. In Indonesia Smart City Index Year 2018, the city of Yogyakarta is ranked third in the medium city category. So that this research in the end will answer the readiness of the City of Yogyakarta as a Smart Tourism Destination. This research is based on three variables, namely, smart service, smart marketing, and smart service management. In this study, the researcher used a qualitative descriptive analysis. Study This study was conducted on July 30, 2019, to August 10, 2019. Participants in the study It is divided into two, namely enterprise and government. Enterprise participants include Museum Fort Vredeburg, Smart Park, Aisya Tour, Zaza Tour, Cabin Hotel, Paku Mas Hotel, Hamzah Batik, Beringharjo Market, and for the government, namely the Yogyakarta City Tourism Office. Results from this study show that enterprises and governments are still not ready to become smart tourism destinations. The results of this study are expected to be an input for the enterprise and the government in the city of Yogyakarta to be able to implement smart tourism in the future